2022
DOI: 10.1038/s41598-022-21035-4
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic, physiological and anatomical responses of soybean plants under water deficit and high temperature condition

Abstract: Water deficit (WD) combined with high temperature (HT) is the major factor limiting agriculture worldwide, and it is predicted to become worse according to the current climate change scenario. It is thus important to understand how current cultivated crops respond to these stress conditions. Here we investigated how four soybean cultivars respond to WD and HT isolated or in combination at metabolic, physiological, and anatomical levels. The WD + HT increased the level of stress in soybean plants when compared … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 92 publications
0
9
0
Order By: Relevance
“…Moreover, temperature and rainfall are considered to be important climatic factors affecting plant growth ( Khan et al., 2022 ; Kharivha et al., 2022 ). In order to adapt to abiotic stresses such as drought, high temperature and low temperature, plants also reduce the impact of climatic conditions on themselves by regulating defense responses ( Akpinar and Cansev, 2022 ; Vital et al., 2022 ). Obviously, when studying the stress of weeds on cotton in the field, extreme climate may have an impact on cotton response to weed stress.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, temperature and rainfall are considered to be important climatic factors affecting plant growth ( Khan et al., 2022 ; Kharivha et al., 2022 ). In order to adapt to abiotic stresses such as drought, high temperature and low temperature, plants also reduce the impact of climatic conditions on themselves by regulating defense responses ( Akpinar and Cansev, 2022 ; Vital et al., 2022 ). Obviously, when studying the stress of weeds on cotton in the field, extreme climate may have an impact on cotton response to weed stress.…”
Section: Discussionmentioning
confidence: 99%
“…Soybean plants of the cultivar "Brasmax ® Power IPRO" were grown in polyethylene pots (10 L), containing 9 kg of a substrate composed of a mix of Red Latosol (LVdf) soil and sand (2:1). Soil base saturation was corrected using limestone (calcium oxide 43-46%, magnesium oxide 6-9%, neutralizing power 95-100%), and the fertilization was performed according to the soil chemical analysis and recommendation for the soybean crop [19]. Plants were grown in growth chambers (Instalafrio, Pinhais, PR, Brazil) with controlled conditions of relative humidity (~65%), irradiance (~650 µmol m −2 s −1 ), and temperature (25/20 • C day/night, 12 h photoperiod), during the development of the plants until the treatment's imposition.…”
Section: Plant Materials and Experimental Conditionsmentioning
confidence: 99%
“…Additionally, drought induced significant alterations in metabolic networks related to tricarboxylic acid cycle, glutamate-mediated proline biosynthesis, glycolysis, shikimate-mediated secondary metabolism and GABA biosynthesis ( Guo et al., 2018 ), suggesting the important role these metabolic pathways play in drought tolerance regulation. Similarly, in soybean ( Glycine max ), myo-inositol and maltose were identified as essential D+H stress biomarkers and were involved in catalase and amino acids biosynthesis pathways ( Vital et al., 2022 ). Additionally, it was observed that under combined D+H stress, network heterogeneity increases whilst integration among metabolic, morphological, and physiological nodes is enhanced ( Vital et al., 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, in soybean ( Glycine max ), myo-inositol and maltose were identified as essential D+H stress biomarkers and were involved in catalase and amino acids biosynthesis pathways ( Vital et al., 2022 ). Additionally, it was observed that under combined D+H stress, network heterogeneity increases whilst integration among metabolic, morphological, and physiological nodes is enhanced ( Vital et al., 2022 ). With metabolite profiles of plant tissues exposed to D/+H revealing a strong relationship between metabolism and grain yield under stress ( Obata et al., 2015 ), such metabolomics studies can provide crucial insights into plant metabolic responses to D/+H stress and reveal novel key potential metabolite biomarkers for engineering D/+H tolerance in cereals ( Obata and Fernie, 2012 ; Michaletti et al., 2018 ; Vital et al., 2022 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation